Prenatal gene-environment interactions mediate the impact of advanced maternal age on mouse offspring behavior - Marta Marlena Ziętek; Aneta Jaszczyk; Adrian Mateusz Stankiewicz; Silvestre Sampino (Scientific Reports)
Abstract Autism spectrum disorders encompass diverse neurodevelopmental conditions marked by alterations in social communication and repetitive behaviors. Advanced maternal age is associated with an increased risk of bearing children affected by autism but the etiological factors underlying this association are not well known. Here, we investigated the effects of advanced maternal age on offspring health and behavior in two genetically divergent mouse strains: the BTBR T+ Itpr3tf/J (BTBR) mouse model of idiopathic autism, and the C57BL/6 J (B6) control strain, as a model of genetic variability. In both strains, advanced maternal age negatively affected female reproductive and pregnancy outcomes, and perturbed placental and fetal growth, and the expression of genes in the fetal brain tissues. Postnatally, advanced maternal age had strain-dependent effects on offspring sociability, learning skills, and the occurrence of perseverative behaviors, varying between male and female offspring. These findings disentangle the relationship between genetic determinants and maternal age-related factors in shaping the emergence of autism-like behaviors in mice, highlighting the interplay between maternal age, genetic variability, and prenatal programming, in the occurrence of neurodevelopmental disorders.